2007
DOI: 10.1080/10304310701460672
|View full text |Cite
|
Sign up to set email alerts
|

Discursive Australia: Refugees, Australianness, and the Australian Public Sphere

Abstract: The Post to Come: an Outline of Post metaphysical Ethics (2005), and her current research turns around the ethico political possibilities and implications of contemporary European philosophy. Her most recent work is published in Philosophy Today and Symposium. Debbie Rodan lectures in the Media & Cultural Studies stream at Edith Cowan University. She has previously published on social and cultural identity formation. Current research projects include: examining the recurring discourses within the letters to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…These contingent sites of social struggles allow dominant and alternative social imaginaries to co-exist. As suggested previously, my analysis re-affirms the widely held view of scholars, such as Mummery and Rodan (2007) and Hartley and Green (2006) about the need to acknowledge the contingent sites of resistance and struggles in the public sphere in relation to Muslims in Australia. However, my analysis contributes to this debate, by unpacking the conditions that make discourse and counterpublics possible.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…These contingent sites of social struggles allow dominant and alternative social imaginaries to co-exist. As suggested previously, my analysis re-affirms the widely held view of scholars, such as Mummery and Rodan (2007) and Hartley and Green (2006) about the need to acknowledge the contingent sites of resistance and struggles in the public sphere in relation to Muslims in Australia. However, my analysis contributes to this debate, by unpacking the conditions that make discourse and counterpublics possible.…”
Section: Resultssupporting
confidence: 77%
“…For instance, the Prime Minister and the New South Wales Police Commissioner made references to the behaviour of the rioters as unAustralian. Similar to the characterizations found in the research of Mummery and Rodan (2007) and Hartley and Green (2006), the discourse was about not engaging in 'rioting', 'respecting the laws', not abusing 'women' and children by letting them carry provocative placards/signs. More pertinently, it is about not behaving in such a way where 'a child is carrying a slogan encouraging murder'.…”
Section: Dominant Publics?mentioning
confidence: 53%
See 1 more Smart Citation
“…Robinson (2008) also notes talk about men used to differentiate (and therefore exclude) bisexual women. Mummery and Rodan (2007) identify this kind of move, in anti-immigration letters, as 'protectivism', whereby the incompatibility between what 'we' are and do, and 'them', is stressed as immutable. Ault (1994) found that (her sample of) lesbians defined bisexuals in male-identified terms, and that for them, 'bisexual women represent the phallus itself' (p. 119).…”
Section: Phase 2: Rejection and Derogation (Topoi 2 And 3)mentioning
confidence: 99%
“…Though readers' letters have typically been considered in the context of newspapers or news magazines, previous research has repeatedly identified letters sections as sites for public opinion articulation, debate and development, and section editors approach their role with this function in mind (Hynds, 1991;Mummery & Rodan, 2007;Wahl-Jorgenson, 2002). In reality, the democratic capability of letters sections is limited by editorial conventions and equal access, among other factors -but this should not dim their discursive significance here, for several reasons.…”
Section: Wouldn't Touch a Bisexual Woman With A Bargepolementioning
confidence: 99%